2021
DOI: 10.15850/amj.v8n2.2282
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices towards the COVID-19 Pandemic among Undergraduate Students

Abstract: Background: Coronavirus disease-2019 (COVID-19) has caused serious implications and has received a lot of international attention, especially in public health sector. The main strategy for containing the COVID-19 pandemic includes preventive methods such as wearing masks, which requires individual awareness and initiative to adhere to the protocol. This study described the level of knowledge, attitude, and practices towards the COVID-19 pandemic among undergraduate students who were selected due to their high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
(17 reference statements)
3
2
1
5
Order By: Relevance
“…In addition, the bodies of people with COVID-19 who have not been buried can be a source of spreading the Covid-19 virus. The facts regarding the low level of student knowledge on aspects of knowledge about the spread of COVID-19 as revealed through this study are also in line with previous research reported by Limbong, et al (2021), Saefi, et al, (2020 & Singh, et al, (2020). Based on these studies, it is found that most students do not understand well that the corona virus can spread in various ways, including through the bodies of infected people.…”
Section: Figure 3 Knowledge Level Regarding Covid-19supporting
confidence: 87%
“…In addition, the bodies of people with COVID-19 who have not been buried can be a source of spreading the Covid-19 virus. The facts regarding the low level of student knowledge on aspects of knowledge about the spread of COVID-19 as revealed through this study are also in line with previous research reported by Limbong, et al (2021), Saefi, et al, (2020 & Singh, et al, (2020). Based on these studies, it is found that most students do not understand well that the corona virus can spread in various ways, including through the bodies of infected people.…”
Section: Figure 3 Knowledge Level Regarding Covid-19supporting
confidence: 87%
“…Pada penelitian ini, pengetahuan mahasiswa tingkat akhir FKUI yang tergolong sangat baik adalah 70%, cukup 30%, dan kurang 0%. Jumlah mahasiswa yang memiliki pengetahuan sangat baik tersebut lebih tinggi dibandingkan pengetahuan masyarakat umum (39,34-56,2%), [4][5][6] populasi mahasiswa Indonesia (35,81%), 7 dan mahasiswa fakultas kedokteran lain (54,1-57,7%), [8][9][10] Pengetahuan kurang sebesar 0% selaras dengan hasil penelitian Limbong et al 11 Tingkat pengetahuan subjek lebih tinggi karena mahasiswa kedokteran memang diberi materi COVID-19 mengingat mereka akan menghadapi pasien secara langsung ketika lulus. Tingkat pengetahuan baik juga menunjukkan bahwa mahasiswa tingkat akhir FKUI memiliki pengetahuan untuk mengedukasi masyarakat.…”
Section: Diskusiunclassified
“…Sebagai contoh, beberapa kuesioner pada penelitian lain ditanyakan aspek pengetahuan mengenai penularan melalui hewan, isolasi, kasus orang tanpa gejala, dan penularan dari mayat COVID-19, sedangkan pada penelitian ini tidak ditanyakan. 6,7,11 Perilaku mahasiswa tingkat akhir FKUI yang tergolong sangat baik adalah 1,9%, cukup 65,7%, dan kurang 32,4%. Jumlah mahasiswa yang memiliki perilaku sangat baik lebih rendah dibandingkan perilaku masyarakat umum (86,15%), 6 mahasiswa universitas dari semua fakultas (67-85,09%) 7,11 dan mahasiswa fakultas kedokteran lain (46,6-51,9%).…”
Section: Diskusiunclassified
See 2 more Smart Citations